Intuitionistic fuzzy G-Congruences on a Lattice - Nair, Latha S (IJRDO -JOURNAL OF MATHEMATICS, 2016)
he definition of reflexivity of a intuitionistic fuzzy relation R on a set S is generalized. Intuitionistic fuzzy equivalence relations on a given set and intuitionistic fuzzy congruence relation on a lattice are studied under this generalized setting. We prove that the set of all intuitionistic fuzzy G-congruence relations on a lattice L forms a lattice, and also we study modularity of a special class of this lattice.